2014
DOI: 10.5861/ijrset.2014.844
|View full text |Cite
|
Sign up to set email alerts
|

The impact of senior citizens’ use of online social networks on their cognitive function

Abstract: The primary purpose of the study was to examine whether senior citizens' use of online social networks affect their cognitive function. For this study, 213 senior citizens who are at least 60 years of age and do not have pre-diagnosed Alzheimer's disease (AD) were randomly selected from a variety of local communities such as a non-AD-patient-retirement home. To measure the cognitive function levels of the selected senior citizens, the Mini Mental State Exam (MMSE), which is the most widely used standardized co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Three studies examined the relationship between SNS use and cognitive function (Kim and Kim, 2014; Myhre et al , 2016; Quinn, 2017), all of which were low (N = 2) or medium quality (N = 1). All studies were limited by their use of convenience samples and small sample size.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies examined the relationship between SNS use and cognitive function (Kim and Kim, 2014; Myhre et al , 2016; Quinn, 2017), all of which were low (N = 2) or medium quality (N = 1). All studies were limited by their use of convenience samples and small sample size.…”
Section: Resultsmentioning
confidence: 99%
“…general internet use, education) and use of an inappropriate test, i.e. they purport to use a t-test to examine relationships (Kim and Kim, 2014). The two remaining studies used an experimental design, with both studies finding beneficial effects of an SNS intervention on aspects of executive function, although the effect disappeared at follow-up in one study (Quinn, 2017).…”
Section: What Is the Association Between Sns Use And Cognitive Function?mentioning
confidence: 99%
“…Research in younger adults has shown that adolescents who used Facebook for longer than one year had higher working memory and verbal abilities compared with adolescents that had been using the site for less time (Alloway, Horton, Alloway, & Dawson, 2013). Kim and Kim (2014) examined social media use and cognition in 213 community dwelling older adults, and observed that online social networking users had significantly higher performance on the Mini Mental State Exam than nonusers. However, once again, because these studies were correlational in nature, it is possible that individuals with higher levels of cognitive function were simply more likely to use online social networking.…”
Section: Introductionmentioning
confidence: 99%
“…Although some evidence links social media use to worse mental health (Krasnova et al, 2013; Wang et al, 2017) and cognitive health outcomes (Frein et al, 2013; Sharifian & Zahodne, 2020b; Soares & Storm, 2018; Tamir et al, 2018), others have found the inverse (Ellison et al, 2007; Kim & Kim, 2014; Myhre et al, 2017). These mixed findings may, in part, be explained by the ways in which different individuals engage with social media.…”
Section: Moderating Role Of Active Versus Passive Usementioning
confidence: 99%